(untitled) (Práxis Educativa, 2009)
This paper presents a research whose objectives were to describe and to analyse the applications of information technology resources – literacy softwares – in a school literacy process. Through a case study, data were collected during pedagogical work sessions, both in the computer room and in the classroom, with a first grade literacy class. The data analysis produced nine Thematical Nucleus, suggesting that the activities of the softwares analysed are founded in a literacy traditional concept, inconsistent with the classroom pedagogical work. Such implications are discussed. Keywords: Literacy. Computer. Educational softwares.